Optimal plot size estimation in field experiment with purple passion fruit - Lopes, Beatriz Garcia; Savian, Taciana Villela; Faria, Glaucia Amorim [UNESP] (FapUNIFESP (SciELO), 2023)
The species P. edulis Sims f. edulis, native to Brazil, known as purple passion fruit, has purple fruits and lower acidity. With the growing demand for passion fruits, there is greater need for research on their cultivation to reduce production costs and improve fruit quality. The adequate determination of the size and number of plots has been a fundamental limitation in studies with several crops, as it is difficult to obtain constant data on plants per plot in most experiments, making it impossible to use usual methodologies for data analysis. As a result, testing can be performed with less labor and implementation costs, making plot size optimization a step of interest. Thus, this work aims to determine the ideal size of experimental plots with purple passion fruit in the field using three methods. The variables analyzed were fruit length, fruit diameter, peel thickness, juice yield, soluble solids content, citric acid, number of fruits, and average fruit weight. The use of optimal plot size of six basic units for fruit-related variables, five for pulp-related variables, and seven basic units for production variables, is recommended.
Estimação do tamanho ótimo de parcela em experimento em campo com maracujá-roxo
Keywords: blank test; experimental planning; maximum curvature; Passiflora edulis Sims f. edulis; quadratic plateau